Stan zachowania wybranych starych druków przechowywanych w Bibliotece Jagiellońskiej : kolekcje oo. kamedułów z Bieniszewa, książąt Sanguszków, oo. reformatów z Biecza - Baumann, Ekaterina (Wydawnictwo Księgarnia Akademicka, 2021)
The work presents results of research on preservation state of three chosen book collections kept in the Jagiellonian Library in Krakow, i.e. the book collections of the Camaldolese Hermits from Bieniszew, princes of the Sanguszko family, and Francis- can Reformates from Biecz. The studies were made with instruments of the methodology of mixed research on the basis of quantitative data obtained by the scoring system method according to a scale. The results were used as a basis for creating the general librarianship model of the evaluation of preservation state of old prints kept in different institutions (public and cloister libraries, private collections). For this model, the following components were defined: structure, list of parameters of book destructions for the assessment in two modes (extended and simplified), as well as significance of the whole list. Furthermore, an optimal scheme of the processing of data, their interpretation and visualisation was proposed. The librarianship model of the evaluation of preservation state of old prints may be used for the determination of conservation work priorities in libraries, assessment of expenditures and obtaining funds for conservation. In this way, it can be used for preservation of the future of cultural property.